2007
DOI: 10.1002/ppul.20731
|View full text |Cite
|
Sign up to set email alerts
|

An experimental model for the measurement of inspired gas temperatures in ventilated neonates

Abstract: Summary. ObjectiveTo determine the inspired gas temperature at points from the endo-tracheal tube (ETT) circuit manifold to the tip of the ETT in a model neonatal lung. Design A model lung attached to standard ventilator circuit, autofeed chamber and humidifier was ventilated using typical pressure-limited, time cycled settings. Temperatures were measured at various distances along the ETT using a K-type thermocouple temperature probe. Results The inspired gas temperature dropped from the circuit temperature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Recently, it has been reported, in an experimental neonatal lung model, that the inspired gas temperature drops in the exposed part of the ETT and the subsequent temperature elevation in the simulated air way and lungs. 15 This demonstration is similar to our present data. Additionally, they speculated that it may well be worth setting the temperature at the circuit temperature probe site even higher (i.e., >408C) to compensate for the drop in the exposed part of the ETT.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, it has been reported, in an experimental neonatal lung model, that the inspired gas temperature drops in the exposed part of the ETT and the subsequent temperature elevation in the simulated air way and lungs. 15 This demonstration is similar to our present data. Additionally, they speculated that it may well be worth setting the temperature at the circuit temperature probe site even higher (i.e., >408C) to compensate for the drop in the exposed part of the ETT.…”
Section: Discussionsupporting
confidence: 94%
“…In studies that used a model lung attached to the ventilator circuit, the results were found to be approximately the same. The mean inspired gas temperatures at the airway opening reaching the model lung were shown to be around ambient or incubator temperature 1,2,10,22,25,26. This result is important for nursing care, because incubator temperatures can be decreased in NICUs, based on the status or the postnatal age of preterm infants who no longer need a higher incubator temperature 27.…”
Section: Discussionmentioning
confidence: 91%
“…In view of this recommendation, humidifier devices are adjusted to 37°C in NICUs. However, recent studies have shown that the set temperature in humidifiers does not reach the airway of the preterm infant 1,2,5,6,20,22. It is therefore suggested that humidifier temperatures should be adjusted to 39°C to 40°C so that the target temperature for infants can be reached 1,5–7,10,11,22,23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that both systems delivered mean temperatures to the patient connection that were 11°C below the target temperature. Jardine, et al [8] found that although there was a slight temperature drop from the set temperature of 40°C at the servo-controlled active heater, the target temperature of 37°C was attained at the proximal end of the endotracheal tube when the unheated portion of the ventilator circuit was removed. The 12-inch unheated section significantly reduces temperature delivery to the patient's artificial airway and subsequently lowers the absolute humidity [6].…”
Section: Discussionmentioning
confidence: 99%